A study on the employability skill possessed by Diploma in Early Childhood Education (DECE) students at SIDMA College / Norhafizah Timpai - Timpai, Norhafizah (2015)
The paper looks into on the DECE student's employability skill. A questionnaire was designed with a sample size of 200 within the area of SIDMA College City Campus. The objectives of this research are to identify the most employability skills perceived by DECE students and to identify which gender perceived the most employability skills. From the findings respondent are perceived on the communications skill. The findings also indicated that female respondent are more perceived on communication skill.